Legal Ambiguity of the Able Requirement for a Husband to Practice Polygamy in Indonesia: Ketidakjelasan Hukum tentang Persyaratan yang Mampu bagi Seorang Suami untuk Melakukan Poligami di Indonesia - Fahmi Shahab; Moch Tanzil Multazam (Academia Open, 2023)
This study examines the meaning of "mampu" or "ability" in Article 5 Paragraph 1 letter (b) of Law No. 1/1974 on Marriage, which serves as a requirement for a husband to practice polygamy in Indonesia. Through a normative legal research method with a statutory approach, the study finds that "mampu" refers to the husband's ability to provide for the needs of his wives and children, including clothing, shelter, and food, based on his income and monthly expenses during his previous marriage. The research emphasizes that "mampu" is a prerequisite for husbands to practice polygamy, ensuring that they can fulfill the needs of all their wives and children while providing legal protection for their first wife and children. Highlights: Study analyzes criteria for polygamy in Indonesia. Husband's ability to provide for family is a key factor. Legal research and deductive methods used for analysis. Keyword: Polygamy in Indonesia, Able requirement, Legal ambiguity, Law No. 1/1974 on Marriage, Normative legal research